A randomized, sham-controlled study of high frequency rTMS for auditory hallucination in schizophrenia. (30th July 2016) - Kimura, Hiroshi; Kanahara, Nobuhisa; Takase, Masayuki; Yoshida, Taisuke; Watanabe, Hiroyuki; Iyo, Masaomi
Abstract: Chronic auditory verbal hallucinations (AVHs) in patients with schizophrenia are sometimes resistant to standard pharmacotherapy. Repetitive transcranial magnetic stimulation (rTMS) may be a promising treatment modality for AVHs, but the best protocol has yet to be identified. We used a double-blind randomized sham-controlled design aimed at 30 patients (active group N=16 vs. sham group N=14) with chronic AVHs that persisted regardless of adequate pharmacotherapy. The protocol was a total of four sessions of high-frequency (20-Hz) rTMS targeting the left temporoparietal cortex over 2 days (total 10, 400 stimulations) administered to each patient. After the rTMS session the patients were followed for 4 weeks and evaluated with the Auditory Hallucination Rating Scale (AHRS). The mean changes of AHRS score were 22.9 (baseline) to 18.4 (4th week) in the Active group and 24.2 (baseline) to 21.8 (4th week) in the Sham group, indicating no significant difference by mix model analysis. As regards other secondary end points (each subscore of AHRS, BPRS, GAF and CGI-S), none of these parameters showed a significant between-group difference. The present study's rTMS protocol was ineffective for our patients. However, several previous studies demonstrated that high-frequency rTMS is a possible strategy to ameliorate pharmacotherapy-resistant AVH. It is important to establish a high-frequency rTMS protocol with more reliability. Highlights: This is a sham-controlled rTMS study for patients with auditory hallucination. A total of four sessions of high-frequency rTMS was delivered to the TP3 junction. The results revealed no beneficial rTMS effect on study's subjects.